How CSR Performance and Financial Report Quality Affect Corporate Share Prices? Case of Indonesia - Suhita Whini Setyahuni (Jurnal Reviu Akuntansi dan Keuangan, 2024)
Purpose: This research intends to investigate the impact of financial report quality and CSR performance on the firm share prices. Methodology/approach: The 78 firms-years observation of LQ-45 public listed companies in Indonesia from 2019 to 2020 is used in this study. The financial report quality is measured by the accrual-based model of earning management, while CSR performance is measured by the amount of CSR spending. The OLS regression is applied to test the hypotheses. Findings: The findings show that there is no effect of financial report quality on the share prices. On the other hand, CSR performance plays an important role in influencing a company’s share prices. CSR performance has a positive effect on share prices. The financial report failed to ensure that there is no existing information asymmetry within the organization. While CSR performance is a form of social-engaged activities in order to achieve social benefits and legitimation. Practical implications: In the context of legitimacy and agency theory, these findings provide fruitful insight into how the firm performance is valued by investors, which is not only based on financial performance but also based on non-financial performance. Originality/value: By providing a new measurement of CSR performance, this study is different to most existing CSR kinds of literature.